2017
DOI: 10.1186/s13048-017-0368-6
|View full text |Cite
|
Sign up to set email alerts
|

A comprehensive overview of exosomes in ovarian cancer: emerging biomarkers and therapeutic strategies

Abstract: Exosomes are nanoparticles(40-100 nm) secreted by most cells in the body, which can be isolated from several types of extracellular fluids. It has been shown that exosomes play a key role in intercellular communication and in transportation of genetic information. Emerging evidence shows that exosomes are mediators of metastasis in tumour cells, stromal cells and the extracellular matrix component through the shuttling of cargo, such as proteins, lipids, RNAs, double-stranded DNAs, non-transcribed RNAs, and mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
65
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 80 publications
0
65
0
Order By: Relevance
“…However, we did not find any coagulation-related differentially expressed genes in our study. As the latest study demonstrated that neural stem/progenitor cell (NSC)-derived EVs function as independent metabolic units that are able to modify the concentrations of critical nutrients, with the potential to affect the physiology of their microenvironment [35], suggesting the low level of cysteine and methionine metabolic enzymes in tumor derived exosomes might be in favor of establishment of tumor microenvironment [12]. Lin et al [36] observed that Glucose-6-phosphate dehydrogenase, transketolase and transaldolase 1, three key enzymes regulated pentose phosphate pathway, were all marked in the same exosomal parts of proteins between two late-stage ovarian cell lines, OVCA429 and HO8910PM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we did not find any coagulation-related differentially expressed genes in our study. As the latest study demonstrated that neural stem/progenitor cell (NSC)-derived EVs function as independent metabolic units that are able to modify the concentrations of critical nutrients, with the potential to affect the physiology of their microenvironment [35], suggesting the low level of cysteine and methionine metabolic enzymes in tumor derived exosomes might be in favor of establishment of tumor microenvironment [12]. Lin et al [36] observed that Glucose-6-phosphate dehydrogenase, transketolase and transaldolase 1, three key enzymes regulated pentose phosphate pathway, were all marked in the same exosomal parts of proteins between two late-stage ovarian cell lines, OVCA429 and HO8910PM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, exosomes have been shown to play a role in immune response, antigen presentation, cell migration, cell differentiation, tumor invasion and other aspects [11]. During the development of cancer, exosomes released from cancer cells are able to transfer a variety of molecules, including those that are cancerspecific, to other cells so as to manipulate their environment, making it more favorable for tumor growth and invasion [11,12]. Recent studies implicate that exosomes can mediate drug resistance in various intracellular processes [13].…”
Section: Introductionmentioning
confidence: 99%
“…EVs are actively involved in cell-to-cell communication, inflammation, chronic disease development and progression, pre-metastatic niche formation, and the metastatic organotropism of different tumor types [8]. Tumor-derived EVs (TEVs) have been reported to play major roles in the onset, progression, and metastasis of cancer, including ovarian [9], breast [10], colorectal [11,12], prostate cancer [13], and melanoma [14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…The quantity of EVs released into circulation is a consequence of the site of origin, and these particles can envelope an extensive plethora of proteomic content. Taking ovarian cancer as an example, over 2000 species of protein have been identified from tumour-derived EVs, including many involved in disease progression and metastasis, such as membrane proteins, tetraspanins, and enzymes [34]. Serum samples were derived from cancer patients with different stages of disease and a range of disease burden as indicated in Table 1.…”
Section: Discussionmentioning
confidence: 99%